FrontEnd Toolkit : A Toolkit to Transform Ideas into Intelligent Action - Barroca, Jean (World Bank, Washington, DC, 2017)
This FrontEnd Toolkit is about applying Design Thinking to transform new ideas into innovative products, services andbusinesses with an impact. The front end development of new user and customer-oriented solutions is a key opportunity aswell as a significant challenge for organizations and success is built on collaborative approaches. The overall objective is to help policy- makers, project owners, and managers as well as their stakeholders to design and implement projects with real impact. The Toolkit helps to establish an idea’s key value to stakeholders, and supports planning for the creation of high impact projects. It assists in defining complexity, cost, delivery, functionality,and future upgrade potential of a concept and creates new opportunities for partnerships. The Front End innovation is all about purposefully combining different skills, disciplines, and resources with knowledge related to the local innovation ecosystem to gain insights that inspire and help shape a new, valuable offering. The process of creating this constellation of elements involves understanding emerging opportunities,client and user mindsets, needs and expectations. It also involves making sense of the competitive environment, the social and individual constraints and enablers that drive the acceptance and up take of new products, services and business models.